f(h(

f(i(

i(

R

↳Dependency Pair Analysis

F(h(x)) -> F(i(x))

F(h(x)) -> I(x)

Furthermore,

R

↳DPs

→DP Problem 1

↳Rewriting Transformation

**F(h( x)) -> F(i(x))**

f(h(x)) -> f(i(x))

f(i(x)) -> a

i(x) -> h(x)

innermost

On this DP problem, a Rewriting SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

F(h(x)) -> F(i(x))

F(h(x)) -> F(h(x))

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳Rw

→DP Problem 2

↳Remaining Obligation(s)

The following remains to be proven:

**F(h( x)) -> F(h(x))**

f(h(x)) -> f(i(x))

f(i(x)) -> a

i(x) -> h(x)

innermost

Duration:

0:00 minutes